2018
DOI: 10.1080/23311886.2018.1514688
|View full text |Cite
|
Sign up to set email alerts
|

Understanding premarital pregnancies among adolescents and young women in Ouagadougou, Burkina Faso

Abstract: In developing countries, young women between 15 and 24 years of age account for more than 40% of unsafe abortions due to the high number of unwanted and/or out-of-wedlock pregnancies. However, much about the profile of adolescents and young women who usually experience premarital pregnancies remains unknown. This study sought to understand the risk of pregnancy before marriage among adolescents and young women in Ouagadougou, Burkina Faso. By using longitudinal data from a demographic surveillance system, we t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 39 publications
2
11
1
1
Order By: Relevance
“…The findings also link nonmarital childbearing chances to household wealth status, whereby women from rich households appear considerably less likely to have a child outside marriage than women from poor households. Women from poor households show a greater risk of nonmarital childbirth and this supports the findings of many related studies in sub-Saharan Africa [ 3 , 18 , 19 , 25 , 26 ]. Women from rich households have a significantly lower risk of unmet need for family planning compared to women from poor households [ 27 ], clearly because they may afford and access sexual and reproductive health services such as family planning and abortion services, information, and education to prevent childbirths outside marriage.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The findings also link nonmarital childbearing chances to household wealth status, whereby women from rich households appear considerably less likely to have a child outside marriage than women from poor households. Women from poor households show a greater risk of nonmarital childbirth and this supports the findings of many related studies in sub-Saharan Africa [ 3 , 18 , 19 , 25 , 26 ]. Women from rich households have a significantly lower risk of unmet need for family planning compared to women from poor households [ 27 ], clearly because they may afford and access sexual and reproductive health services such as family planning and abortion services, information, and education to prevent childbirths outside marriage.…”
Section: Discussionsupporting
confidence: 89%
“…Older women have a disproportionately higher likelihood of nonmarital childbearing within the sample. Some similar studies in sub-Saharan Africa such as Namibia [ 18 ], Nigeria [ 19 ], Burkina Faso [ 25 ], and South Africa [ 28 ] also provide evidence on the positive association between women’s age and nonmarital childbearing risks. This is likely because, in sub-Saharan Africa, particularly Ghana, many older or aging women who are still unmarried may likely give up on marriage and focus on having children outside marriage if they feel they can successfully cater for them.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“… 2-4 Youths usually engage with early sexual debut to experiment sex before marriage. 1 , 5 Early sexual activity within a passionate relationship could increase expectations of early marriage and childbearing with its several potential impacts on reproductive life. 2 , 6 , 7 …”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] Youths usually engage with early sexual debut to experiment sex before marriage. 1,5 Early sexual activity within a passionate relationship could increase expectations of early marriage and childbearing with its several potential impacts on reproductive life. 2,6,7 Evidence indicated that those students who engaged early sexual debut are exposed to risky sexual behaviours such as unprotected sexual intercourse, multiple sexual partners and incorrect or inconsistent condom use leading to HIV/AIDS, sexually transmitted infection (STIs), unwanted pregnancies, unsafe abortion, early childbirth, and psychosocial problems.…”
Section: Introductionmentioning
confidence: 99%